Sustainable Development: Case Study of Customary Law and Land Acquisition Rejection in Kekeran Village - Ni Made Ayu Nindya Damayanti; Moh. Mudzakkir; Putri Dwi Permata Indah; Sugeng Harianto (Journal of Southern Sociological Studies, 2026)
Kekeran Village maintains a robust customary policy to protect its living space, specifically through the traditional prohibition of selling agricultural land to external parties. This study aims to analyze the strategies of the Kekeran indigenous community in navigating land acquisition pressures from investors and preserving their agrarian sovereignty. Utilizing a descriptive qualitative approach, data were gathered through participatory observation, documentary studies of awig-awig regulations, and in-depth interviews with customary leaders. Max Weber’s social action theory is applied to examine the motives underlying community resistance. The results indicate that the rejection of land acquisition is an integration of value-rational and traditional actions, where land is perceived as a spiritual identity transcending economic commodity value. Collective strategies identified include strengthening social bonds, tightening customary sanctions, and synchronizing local rules with government regulations. In conclusion, local sovereignty supported by adherence to customary law is the primary key to achieving inclusive sustainable development. The synergy between technocratic policies and local wisdom effectively minimizes land conversion for the welfare of future generations.